The use of social networks in educational computer-game based foreign language learning - Donmus, Vildan (Elsevier Science Bv, 2010)
Individuals spend much time on games in order to get rid of the boredom of their daily lives. With the introduction of computers into our lives, computer based games and after, internet based games, have started to be used widely in order our lives be much more exciting and interesting. Despite continuing change in education, games are indispensible part of education all the time and the concept of educational game has come into use in education world today. The value of educational games has been increasing in language education since they help to make language education entertaining. Like the popularity of educational games, social networks are also popular in today's world. The aim of this study to put a light on using educational games with the support of social networks in foreign language education. (C) 2010 Published by Elsevier Ltd.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: social network; educational computer game; foreign language learning